Improving Early Childhood Communication Skills: An Analysis of Influence of Spin Tamadun Game Media - Sisylia Nur Mar'Atus Sholihah; Dwi Istiyani; Neisya Azaria Adinda Putri (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2025)
This study aims to describe the use of the Spin Tamadun game in improving early childhood communication skills through Islamic history learning at KB/TK Islam Miftahul Jannah Semarang. The problem addressed is the low ability of children to express opinions, respond to questions, and use new vocabulary actively in learning activities. This research employed a descriptive qualitative approach using observation, interviews, and documentation techniques involving 15 children aged 5–6 years over four meetings. The results show an improvement in children’s communication abilities, indicated by an increased vocabulary range, greater confidence in speaking, and more active participation in class discussions and question–answer sessions. Spin Tamadun successfully created an enjoyable, interactive, and contextual learning atmosphere that encouraged children to express ideas both verbally and nonverbally with higher confidence. Therefore, Spin Tamadun serves as a simple yet effective educational medium to stimulate language development, speaking confidence, and communication skills in early childhood through meaningful and enjoyable learning experiences.Keywords: Spin Tamadun, children's communication, Islamic history learning. ABSTRAK. Penelitian ini bertujuan mendeskripsikan penggunaan permainan Spin Tamadun dalam meningkatkan kemampuan komunikasi anak usia dini melalui pembelajaran Sejarah Islam di KB/TK Islam Miftahul Jannah Bringin Kota Semarang. Permasalahan yang diangkat ialah rendahnya kemampuan anak dalam hal komunikasi, menyampaikan pendapat, merespon pertanyaan, serta menggunakan kosakata baru secara aktif dalam kegiatan belajar. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik observasi, wawancara, dan dokumentasi terhadap 15 anak berusia 5-6 tahun selama empat kali pertemuan. Hasil penelitian menunjukkan adanya peningkatan kemampuan komunikasi anak yang ditandai dengan bertambahnya kosakata, meningkatnya keberanian berbicara, serta partisipasi aktif dalam kegiatan diskusi dan tanya di kelas. Spin Tamadun terbukti mampu menicptakan suasana belajar yang menyenangkan, interaktif, dan kontekstual, sehingga mendorong anak untuk berani mengemukakan ide secara lisan maupun nonverbal dengan lebih percaya diri. Dengan demikian, Spin Tamadun berperan sebagai media edukatif yang sederhana namun efektif untuk menstimulasi perkembangan bahasa, keberanian berbicara, dan kemampuan komunikasi anak usia dini dalam konteks pembelajaran yang bermakna dan menyenangkan.Kata Kunci:  Spin Tamadun, Komunikasi anak, Pembelajaran Sejarah Islam.